Performance-based fire behaviour analysis for underground parking structures. Issue 1 (27th May 2016) - Heo, Inwook; Kang, Hyun; Lee, Deuck Hang; Oh, Jae-Yuel; Lee, Jungmin; Kim, Kang Su
ABSTRACT: The current design code for building structures in South Korea specifies the minimum fire resistance ratings and fire-resisting performances for each structural component, for which a standard fire curve is required to be applied. There are, however, obvious differences between the standard fire curve and the actual fire behaviour observed from real events. In this study, a fire dynamic-based simulation was conducted on a typical underground parking structure, from which a realistic fire design curve was obtained. In addition, thermal behaviour and fire-resisting response of hollow-core slabs in the underground parking structure were estimated by using the realistic fire design curve, which was compared to those based on the design fire curve specified in the current code. On this basis, it is considered that more rational and economic fire resistance design of underground parking structure is possible by utilizing the realistic fire curve.